The roles of promotional tools on the evaluation tax compliance in Jasin District Council (MDJ), Melaka: Mukim Jasin / Ahmad Rafaie Abdullah - Abdullah, Ahmad Rafaie (Faculty of Business and Management, 2004)
The purpose of this research is to study the roles of promotional tools on evaluation tax compliance in Jasin District Council (MDJ); Mukim Jasin. It also would examine and measure the trends of evaluation tax compliance and the roles of promotional tools in order to enhance the evaluation tax compliance in the areas. The findings showed that increasing trends of evaluation tax revenue and tax accrued for the period 1990-2002. There are various factors that contributed to these trends such as economic condition, taxes management, policies, and strategies. Researcher also would measured the effectiveness of promotional tools that used by MDJ and divergence of importance for each tool. The findings also showed that taxpayers expected to get optimum services such as better services, better physical development, better infrastructures and better environment once they have complied their responsibilities. In this study, there were used interviews and questionnaire techniques and others secondary data such as reports, database, and so on. Based on frequencies and cross tabulations analysis, there showed a clear observation about the findings of this study.